Laccases 2 & 3 as biomarkers of Botrytis cinerea infection in sweet white wines. (15th June 2020) - Ployon, S.; Attina, A.; Vialaret, J.; Walker, A.S.; Hirtz, C.; Saucier, C.
Highlights: Five B. cinerea laccases were identified in sweet white wines. A LC–MS/MRM method targeting laccase-2-BcLCC2 and laccase-3-BcLCC7 was developed. Laccase-2-BcLCC2 and laccase-3-BcLCC7 were in higher amount in botrytized wines. Abstract: Botrytized sweet wines are made with berries infected by the fungus Botrytis cinerea . The aim of this study was to identify biomarkers of B. cinerea infection in sweet wines with a focus on laccases which are exocellular oxidase enzymes produced by this fungus during fruit contamination. Total proteins from six commercial sweet wines, including three naturally botrytized wines and three non-botrytized wines were analysed by LC-QTOF-MS. Five laccases, namely laccase-1-BcLCC1, laccase-2-BcLCC2, laccase-3-BcLCC7, laccase-8-BcLCC8 and laccase-12-BcLCC12, were identified in both types of wine. Then, a targeted proteomic approach by LC-MRM was used to semi-quantify laccase-2-BcLCC2 and laccase-3-BcLCC7, in the six samples. LC-MRM targeted analysis of the two enzymes allowed the discrimination of botrytized versus non-botrytized sweet white wines.